2017
DOI: 10.1016/j.imlet.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical activity in the anti-tumor immune response in experimental breast tumor

Abstract: This study aimed to investigate the influence of physical activity in innate immunity to conduce to an effective antitumoral immune response analyzing the phenotype and activation status of infiltrating cells. We analysed the intracellular cytokines and the transcription factors of tumor infiltrating lymphocytes (TILS) and spleen leukocytes. The Nos2 gene expression was evaluated in spleen cells and futhermore the ROS production was measured and spleen cells; another cell evaluated was dendritic cells (TIDCs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
1
27
0
3
Order By: Relevance
“…Interruption of training after inoculation of tumor cells favored tumor growth similarly to the full-time sedentary group. Corroborating our results, Bianco and colleagues [24] showed that forced swimming exercise reduced tumor volume in animals inoculated with 2 × 10 5 4T1 cells. In addition, voluntary physical exercise has been shown to reduce tumor growth rate after mice were inoculated with 5 × 10 4 [22] or 1 × 10 4 [23] 4T1 cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interruption of training after inoculation of tumor cells favored tumor growth similarly to the full-time sedentary group. Corroborating our results, Bianco and colleagues [24] showed that forced swimming exercise reduced tumor volume in animals inoculated with 2 × 10 5 4T1 cells. In addition, voluntary physical exercise has been shown to reduce tumor growth rate after mice were inoculated with 5 × 10 4 [22] or 1 × 10 4 [23] 4T1 cells.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations of the effects of physical exercise on experimental TNBC are still scarce and wield heterogeneous results [22][23][24][25][26]. Here we showed that moderate aerobic physical training, both 8 weeks before and 4 weeks after the inoculation of 4T1 cancer cells, reduces tumor growth.…”
Section: Discussionmentioning
confidence: 62%
“…Nineteen studies investigated the effect of PA interventions on cancer immune outcomes using preclinical breast cancer models ( Table 1 ). Transplantable tumor models were used in 14 studies ( 31 , 32 , 34 , 35 , 44 50 , 53 55 ), among which six used the 4T1 (or its subclone 4T1.2) TNBC murine mammary tumor model ( 32 , 34 , 35 , 44 , 48 , 54 ). Carcinogen-induced ( n = 3) ( 33 , 56 , 57 ) and genetically-engineered/spontaneous ( n = 2) ( 51 , 52 ) mammary tumor models were also used.…”
Section: Resultsmentioning
confidence: 99%
“…Adicionalmente, em modelo experimental de melanoma, demonstrou-se que o exercício foi capaz de realçar o conteúdo de células NK, com consequente redução do tamanho tumoral (Pedersen et al, 2016). Entretanto, nenhuma alteração no infiltrado de linfócitos foi observada após exercício físico em meio aquático com modelo experimental de câncer de mama (Bianco et al, 2017). Além disso, estima-se que o exercício aeróbico pode melhorar a perfusão e amenizar a hipoxia tumoral via estímulos angiogênicos e redução na expressão de HIF's em modelos xenográficos de câncer de mama (Betof et al, 2015;Khori et al, 2015;Isanejad et al, 2016;Wiggins et al, 2018).…”
Section: Microambiente Tumoralunclassified
“…semanas-3 e 4), cinco dias por semana durante quatro semanas, teve impacto positivo na redução do volume tumoral em animais inoculados com cinco vezes menos células (i.e. 2x10 5 células 4T1) (Bianco et al, 2017). É importante destacar que em nosso estudo, com exercícios forçados em esteira, tanto o protocolo de treinamento, como a inoculação de células tumorais (i.e.…”
Section: Impacto Do Exercício Físico Aeróbico Sobre O Volume E Massa unclassified